PENGARUH PROPORSI KOMISARIS INDEPENDEN, KOMITE AUDIT, PREFERENSI RISIKO EKSEKUTIF DAN UKURAN PERUSAHAAN PADA PENGHINDARAN PAJAK - Trisna Yudi Asri, Ida Ayu; Suardana, Ketut Alit (E-Jurnal Akuntansi; Vol 16 No 1 (2016), 2016)
The use of self ass c essment system in Indonesia to deliver benefits taxpayer to calculate the taxable income to minimum. One of the actions taken by taxpayers to reducing or minimizing duty tax carefully to take advantage loopholes of tax law. This research has a purpose analyzed and verify about proportion of independent directors, presence of audit committee, executive risk preferences and firm size on tax avoidance in manufacturing companies listed in Indonesia Stock Exchange 2011-2013. The sample is determined by utilizing purposive sampling technique therefore as many as 159 of observation sample was obtained. The data observed with multiple linear regression analysis method. Results show that presence of audit committee, executive risk preferences and firm size has effect on tax avoidance. While proportion of independent directors did not has effect on tax avoidance.
Keywords: tax avoidance, proportion of independent directors, presence of audit committee, executive risk preferences, firm size